Analytical and numerical calculation and simulation of heat transfer in a composite wall made of polyethylene terephthalate bottle - Martial Ngnihamye Nde; Seydou Youssoufa; Fabien Kenmogne; Elvis Mbou Tiaya; Thierry Simo; Leaticia. Ekoro Ottou; Michel Mbessa; Emmanuel Yamb Bell (Alexandria Engineering Journal)
The dynamics of heat transfer in composite walls made of Polyethylene Terephthalate (PET) bottles is studied using the energy conservation model. Ten walls of different structures were studied, including two control walls made of compressed earth brick (CEB) and cementitious material, cement-sand brick (CSB) and eight composite walls made of PET bottles filled with thermal insulation and/or mechanical stabilisation materials. The model equation is solved analytically using the separation of variables method and numerically using the finite difference method, and they are confirmed using CASTEM finite element software. As boundary conditions, a constant temperature (Text) is applied at one end of the wall, and the constant temperature (T0) is applied at any other point at the initial time. The effect of PET bottles filling on the thermal behaviour of the wall was then carried out to determine the optimum design that would give the wall better thermal inertia. The results obtained with CASTEM is fairly in agreement with the results obtained analytically and numerically, with a maximum relative error closed to that of the spatial evolution and 3.310−2 for the temporal one. It is found that heterogeneous filling of PET bottles provides better thermal inertia at the wall.